Morphological and cytotaxonomic data of Allium trichocnemis and A. seirotrichum (Amaryllidaceae) endemic to Northern Algeria, compared with A. cupanii group - Khedim, Thinhinan; Amirouche, Nabila; Amirouche, Rachid (Phytotaxa, 2016)
In this study two rare species of Allium, endemic to Northern Algeria, namely A. trichocnemis and A. seirotrichum are examined from morphological, karyological, chorological and ecological point of view. The chromosome complements of these species are reported here for the first time. Taxonomical comparison with the allied species (A. cf. cupanii and A. cf. hirtovaginatum) occurring also in Algeria are carried out too.